Harmonising engineering and landform design for integrated rehabilitation and closure planning: a case study - Koekemoer, L; van Wyk, G (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
As the global demand for minerals keeps rising, the mining industry plays a pivotal role in meeting these demands while adhering to the United Nations Sustainable Development Goals. This case study explores the intersection of engineering and landform design in terms of sustainable mining practices. The case study pertains to the waste rock dump of a diamond mine in Botswana and was driven by the socioeconomic needs of the local population. A reduction in the overall liability and promotion of a sustainable development was sought, in tandem with resource extraction that adhered to associated legislation and ensured a stable landform suitable for the proposed end land use. This was achieved by conducting a staged approach. The first stage involved conducting soil erosion studies on the site-specific extricated mine residue materials. These studies involved two primary phases: chemical testing and erodibility testing. Chemical testing assesses parameters such as pH, electrical conductivity, nutrient levels, trace elements, organic carbon and particle size distribution. Erodibility testing involves simulated rainfall experiments to evaluate soil susceptibility to erosion. These datasets are used to calibrate erosion models like the water erosion prediction project and inform landform and cover designs. The second stage consisted of utilising the results of the soil erosion studies, whereby these results guided a dumping strategy design including a range of batter geometry designs and shapes (uniform gradient, concave gradient), slope gradients and lengths, final cover designs and, ultimately, the final landform design. The last stage involved ensuring outputs met regulations and stakeholder expectations while integrating environmental and socio-economics factors into the landform design for long-term sustainability and positive community relations. In conclusion, the case study showcases how integrating engineering and landform design promotes sustainable mining practices. The project mitigated erosion risks, minimised earthworks during operations and closure, created opportunities for concurrent rehabilitation, and ultimately ensured a stable landform and a reduction in liability.
Keywords: sustainable mining